Pengujian Black Box pada Aplikasi Perpustakaan Menggunakan Teknik Equivalence Partitions - Bayu Aji Priyaungga; Dwi Bayu Aji; Mukron Syahroni; Nurul Tri Sukma Aji; Aries Saifudin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
The library application is used to help manage and document transaction activities in the library which include borrowing and repaying. Library applications must be free of errors, because if they contain errors can cause harm to providers, managers, or members of the library. To provide a guarantee that the library application is free from errors, testing needs to be done. Software testing is an activity aimed at finding and finding errors and bugs in an application, which aims to minimize the losses that occur due to system errors. In this study, the proposed library application testing is Black Box. Black Box Testing is a test based on the appearance (interface) and functions of the software itself and not from the source code of the program. Black Box Testing has several methods, one of which is Equivalence Partitions, the method we use for testing the software. Equivalence Partitions are methods that discuss valid or not entered into the software, and observe the accuracy of the input. So that the side of the error is known. The test results have proven that the library application that has been developed is error free and meets all the requirements set.